ANALYSIS OF ONLINE MEDIA FRAMING DURING INDONESIA'S EMERGENCY WARNING - Agus Priyanto; Al Fauzi Rahmat; Fadri Ari Sandi (Halu Oleo University, 2025)
Indonesia was in an uproar over the issuance of an emergency alert, something that had never previously occurred in the form of a demonstration. Typically, emergency alerts in Indonesia are issued due to natural disasters. The author aims to examine how online media framed this emergency alert, which drew significant public attention in Indonesia. This study employs a qualitative descriptive method, utilising primary data from news reports published by online media in Indonesia. Data processing is conducted using the NVIVO application to analyse the news from these media sources. The framing analysis of online news articles reveals that the phrase “Expression Of Aspirations” appeared most frequently. Based on the coding results, it can be concluded that before the large-scale and rapid demonstration took place, online media framed their news coverage around the theme of expressing aspirations, which ultimately led to a massive public demonstration.